Multiple symbol soft-output non-coherent detection of serial concatenated CPM - You-fu YANG; Jian-wei LIU; Qi-shan ZHANG; Chun-di XIU (Tongxin xuebao)
A non-coherent detection algorithm for CPM was proposed.Several sequential symbols were used as the observation window to calculate the prior probability for codeword in CPM soft demodulation process,and the more observation symbols were used,the better performance the algorithm achieved.Non-coherent receiver architecture was given,in which expansion method of Walsh basis function was utilized to reduce the calculating amount in matched filtering.Non-coherent detection performances of convolutional encoding CPM system adopting the proposed algorithm,with different CPM modulation parameters,were compared through simulation.The results indicate that proposed non-coherent detection algorithm brings significant robustness.As to 2CPM,4CPM serial concatenated encoding modulation,when the observation length gets to 4 symbols,system with the proposed algorithm gets nearly 6dB performance improvement than with the single-symbol non-coherent detection algorithm.